2007
DOI: 10.1007/s11199-007-9318-x
|View full text |Cite
|
Sign up to set email alerts
|

Contesting and Maintaining Hegemonic Masculinities: Gay Asian American Men in Mate Selection

Abstract: Masculinity is a prized commodity in mate selection among gay men. However, few studies systematically examine how gay Asian American men interpret their form of masculinity in the context of mate selection. Using data from in-depth interviews with 37 Asian Americans, I study how they interpret and negotiate their form of masculinity within a racialized gender hierarchy. The results show gay Asian American men maintain the hegemonic masculinity frame in the negotiation of their desirability and desires. Concur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 23 publications
2
65
0
Order By: Relevance
“…For example, research in social psychology has documented powerful effects of stereotypes on human behavior and self-identification (Chen & Bargh, 1997;Galinsky et al, 2013;Kelly & Floyd, 2001;Skrypnek & Snyder, 1982). Moreover, several recent studies documented that some gay men feel pressure to fulfill stereotypes associated with their racial group (Han, 2006;Phua, 2007). Coupled with the current findings, this work raises the possibility that stereotypes and perceptual biases may lead Asian men to align themselves with the bottom role and Black men to align themselves with the top role.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…For example, research in social psychology has documented powerful effects of stereotypes on human behavior and self-identification (Chen & Bargh, 1997;Galinsky et al, 2013;Kelly & Floyd, 2001;Skrypnek & Snyder, 1982). Moreover, several recent studies documented that some gay men feel pressure to fulfill stereotypes associated with their racial group (Han, 2006;Phua, 2007). Coupled with the current findings, this work raises the possibility that stereotypes and perceptual biases may lead Asian men to align themselves with the bottom role and Black men to align themselves with the top role.…”
Section: Discussionsupporting
confidence: 66%
“…For example, Han (2006) argued that gay men enact gendered stereotypes associated with their racial identity, such that Black men display a dominant, masculine form of sexuality (e.g., topping) whereas Asian men display a submissive, feminine form of sexuality (e.g., bottoming). Furthermore, Phua (2007) documented that some Asian gay men deliberately fulfill feminine stereotypes in order to attract mates who expect Asian men to be submissive. Thus, previous research suggests that links between race, gender, and sexual roles may be evident in gay men's self-presentations.…”
Section: Sexual Scripting Theory and Sexual Role Preferencesmentioning
confidence: 99%
“…In fact, numerous studies focused on gay men's personal advertisements have found that a large proportion of gay advertisers overtly claim to possess masculine traits (e.g., being interested in sports, preferring beers over colorful cocktails, and purporting to be''straight acting'') and that they desire masculine mates (Bailey, Kim, Hills, & Linsenmeier, 1997;Bartholome, Tewksbury, & Bruzzone, 2000;Phua, 2007). This desire is also reflected in the postings of online sites geared towards facilitating sexual encounters (Logan, 2010;Ward, 2008) and in gay erotica (Joshi, 2003;Morrison, 2004).…”
Section: Masculinity and Anti-effeminacy Among Gay Menmentioning
confidence: 99%
“…The concern of the study was to explore how the instances of anti-Asian sentiment identified on the profiles drew upon highly normative understanding of masculinity that were both racialised and sexualized, and which functioned to construct gay Asian men as effeminate or as otherwise outside the category 'man.' Such constructions are considered to be clear examples of the potentially injurious nature of public speech which may impact negatively upon the identities of gay Asian men by reinforcing the racialised power differentials that exist between White and Asian gay men, as has been noted in previous research on gay Asian American men's experiences of masculinity (Phua, 2007).…”
Section: Introductionmentioning
confidence: 97%